Perspectives of people living with idiopathic pulmonary fibrosis: a qualitative and quantitative study - Camilla S. Graham; Brianna Bisson; Jessica Shore; Emily Pardy; Frank Salisbury; Lisa Lancaster; Tejaswini Kulkarni (BMC Pulmonary Medicine)
Abstract Background The antifibrotic therapies, pirfenidone and nintedanib, have been approved since 2014 for idiopathic pulmonary fibrosis (IPF), but in the United States only a quarter of people living with IPF have ever been exposed to an antifibrotic. Understanding the burden and consequences of the disease and its treatment from the perspective of people living with IPF may facilitate improved education and outreach for them and their providers. Methods Qualitative interviews with people living with IPF explored perspectives on the diagnosis and management of IPF. Transcripts were analyzed to derive themes and topics, and illustrative quotes were selected for presentation. Data were developed into a 74-item on-line survey taken by additional people living with IPF. Quantitative survey data were analyzed with 95% confidence intervals and Z tests. Results Sixteen people living with IPF underwent qualitative interviews. Direct quotes were used to derive and support themes, and survey stimuli are presented. Ninety additional people living with IPF responded to the on-line survey. 52% of survey participants were male, 54% used supplemental oxygen, and 34% had never been exposed to an antifibrotic. Top sources of information about their IPF diagnosis were their healthcare provider, the internet, and support groups. Most participants had one or more of shortness of breath, fatigue, or cough and over 40% described these symptoms as very burdensome. The most common reason for not starting an antifibrotic was, “I am waiting to start treatment until my symptoms worsen.” For those treated with antifibrotics, (78%) agreed with a statement that their antifibrotic gives them hope even though around 90% had at least one side effect. Conclusions Most individuals living with IPF experienced significant challenges due to their disease and its treatment, that substantially impacted their quality of life. A better understanding of these challenges can facilitate patient-centered and shared decision-making, ultimately enhancing outcomes and satisfaction for people living with IPF.